Advances in hybrid solar cells: from dye-sensitised to perovskite solar cells - Noel, NK (2014)
This thesis presents a study of hybrid solar cells, specifically looking at various methods which can be employed in order to increase the power conversion efficiency of these devices. The experiments and results contained herein also present a very accurate picture of how rapidly the field of hybrid solar cells has progressed within the past three years. Chapters 1 and 2 present the background and motivation for the investigations undertaken, as well as the relevant theory underpinning solar cell operation. Chapter 2 also gives a brief review of the literature pertinent to the main types of devices investigated in this thesis; dye-sensitised solar cells, semiconductor sensitized solar cells and perovskite solar cells. Descriptions of the synthetic procedures, as well as the details of device fabrication and any measurement techniques used are outlined in Chapter 3. The first set of experimental results is presented in Chapter 4. This chapter outlines the synthesis of mesoporous single crystals (MSCs) of anatase TiO2 as well as an investigation of its electronic properties. Having shown that this material has superior electronic properties to the conventionally used nanoparticle films, they were then integrated into low temperature processed dye-sensitised solar cells and achieved power conversion efficiencies of > 3%, exhibiting electron transport rates which were orders of magnitude higher than those obtained for the high temperature processed control films. Chapter 5 further investigates the use of MSCs in photovoltaic devices, this time utilising a more strongly absorbing inorganic sensitiser, Sb2S3. Utilising the readily tunable pore size of MSCs, these Sb2S3 devices showed an increase in voltage and fill factor which can be attributed to a decrease in recombination within these devices. This chapter also presents the use of Sb2S3 in the meso-superstructured configuration. This device architecture showed consistently higher voltages suggesting that in this architecture, charge transport occurs through the absorber and not the mesoporous scaffold. Chapters 6 and 7 focus on the use of hybrid organic-inorganic perovskites in photovoltaic devices. In Chapter 6 the mixed halide, lead-based perovskite, CH3NH3PbI3-xClx is employed in a planar heterojunction device architecture. The effects of Lewis base passivation on this material are investigated by determining the photoluminescence (PL) lifetimes and quantum efficiencies of treated and untreated films. It is found that passivating films of this material using Lewis bases causes an increase in the PLQE at low fluences as well as increasing the PL lifetime. By globally fitting these results to a model the trap densities are extracted and it is found that using these surface treatments decreases the trap density of the perovskite films. Finally, these treatments are used in complete solar cells resulting in increased power conversion efficiencies and an improvement in the stabilised power output of the devices. Chapter 7 describes the materials synthesis and characterisation of the tin-based perovskite CH3NH3SnI3 and presents the first operational, lead-free perovskite solar cell. The work presented in this thesis describes significant advances in the field of hybrid solar cells, specifically with regards to improvements made to the nanostructured electrode, and the development and implementation of more highly absorbing sensitizers. The improvements discussed here will prove to be quite important in the drive towards exploiting solar power as a clean, affordable source of energy.